Gene expression of bovine embryos developing at the air-liquid interface on oviductal epithelial cells (ALI-BOEC). Issue 1 (December 2017) - van der Weijden, Vera; Chen, Shuai; Bauersachs, Stefan; Ulbrich, Susanne; Schoen, Jennifer
Abstract We recently developed an air-liquid interface long-term culture of differentiated bovine oviductal epithelial cells (ALI-BOEC). This ex vivo oviduct epithelium is capable of supporting embryo development in co-culture up to the blastocyst stage without addition of embryo culture medium. However, blastocyst rates in co-culture were markedly lower than in conventional in vitro embryo production procedures. In the present study, we assessed target gene expression of ALI-BOEC derived embryos to test their similarity to embryos from conventional in vitro embryo culture. We screened previously published data from developing bovine embryos and selected 41 genes which are either differentially expressed during embryo development, or reflect differences between various in vitro culture conditions or in vitro and in vivo embryos. Target gene expression was measured in 8-cell embryos and blastocysts using a 48.48 Dynamic Array™ on a Biomark HD instrument. For comparison with the ALI-BOEC system, we generated embryos by two different standard IVP protocols. The culture conditions lead to differential gene expression in both 8-cell embryos and blastocysts. Across the expression of all target genes the embryos developing on ALI-BOEC did not depart from conventional IVP embryos. These first results prove that gene expression in ALI-BOEC embryos is not largely aberrant. However, there was no clear indication for a more in vivo-like target gene expression of these embryos. This calls for further optimization of the ALI-BOEC system to increase its efficiency both quantitatively and qualitatively.